An Overview on Time‐Resolved Optical Analysis of HiPIMS Discharge. Issue 9 (2nd June 2015) - Britun, Nikolay; Konstantinidis, Stephanos; Snyders, Rony; Fouquet, Thierry; Girard‐Lauriault, Pierre‐Luc
<x xml:space="preserve">Abstract</x> The progress in the time‐resolved characterization of HiPIMS discharges performed during the last decade in our group is overviewed. Optical emission and absorption spectroscopy, as well as laser‐induced fluorescence‐based techniques have been mainly utilized. The results covering such important aspects of the HiPIMS discharge as the density evolution of the discharge species, their ionization and excitation, propagation of secondary electrons in the discharge volume, dynamics of velocity distribution of the discharge species, gas rarefaction, etc. are discussed.<inline-graphic xlink:href="ark:/27927/pgj2ntc6dmd" content-type="ppap201500051-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />